2014
DOI: 10.1128/aem.01782-14
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides Synthesized by Lactobacillus reuteri Protect against Enterotoxigenic Escherichia coli in Piglets

Abstract: bEnterotoxigenic Escherichia coli (ETEC) is a major cause of diarrhea in piglets; ETEC cells colonize the intestinal mucosa with adhesins and deliver toxins that cause fluid loss. This study determined the antiadhesive properties of bacterial exopolysaccharides (reuteran and levan) and related glycans (dextran and inulin) in a small intestinal segment perfusion (SISP) model. The SISP model used 10 jejunal segments from 5-week-old piglets. Five segments were infected with ETEC expressing K88 fimbriae (ETEC K88)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 49 publications
3
48
0
2
Order By: Relevance
“…Specifically, the reuteran produced by L. reuteri TMW1.656 reduces the adhesion of ETEC K88. In the present study, the reuteran-positive groups had lower copy numbers of genes for E. coli and the ETEC virulence factors than groups fed diets containing L. reuteri but not reuteran or levan, which may reflect the antiadhesive properties of reuteran in vitro (16) and in an in vivo model (17). Together with the findings presented in those prior reports, this study suggests that reuteran reduces the level of ETEC adhesion to the intestinal mucosa in vivo.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Specifically, the reuteran produced by L. reuteri TMW1.656 reduces the adhesion of ETEC K88. In the present study, the reuteran-positive groups had lower copy numbers of genes for E. coli and the ETEC virulence factors than groups fed diets containing L. reuteri but not reuteran or levan, which may reflect the antiadhesive properties of reuteran in vitro (16) and in an in vivo model (17). Together with the findings presented in those prior reports, this study suggests that reuteran reduces the level of ETEC adhesion to the intestinal mucosa in vivo.…”
Section: Discussionsupporting
confidence: 77%
“…ETEC adhesion in vitro was also reduced by reuteran and levan, exopolysaccharides produced by Lactobacillus reuteri (16). The protective effect of reuteran was confirmed in vivo in the small intestinal segment loop perfusion model (17). Evidence for the effectiveness of probiotic cultures or antiadhesive glycans for the prevention of ETEC infection in vivo, however, remains limited.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…To purify glucans produced by L. reuteri TMW1.656, the strain was cultured in sucrose mMRS broth for 16 h and subcultured overnight in 1 L sucrose-mMRS broth. Reuteran was harvested via 2 volume ethanol precipitation and purified by dialysis as described (Chen et al, 2014). The retentate was freeze dried and stored at −20°C.…”
Section: Glucan Production and Purificationmentioning
confidence: 99%
“…One study evaluated the effects of bifidobacteria and LAPB (in place of AGPs) in newborn calves and piglets and demonstrated that these probiotics reduced mortality, improved weight gain, fecal condition and feed efficiency in both species (Abe et al, 1995). However, the effects of lactobacilli (including various strains of L. reuteri , as well as L. gasseri , L. acidophilus and L. fermentum ) supplementation on infectious diarrhea occurrence, growth performance and feed conversion in neonatal and weanling piglets varied with age, feeding status (sow milk versus milk replacer) and lactobacilli strain (Chang et al, 2001; Chen et al, 2014; Huang, 2004; Liu et al, 2014; Wang et al, 2009a; Wang et al, 2013; Wang, 2011; Wang et al, 2012; Yu, 2008) (Table 3). Potential mechanisms of lactobacilli beneficial effects proposed in these studies included alleviation of oxidative stress (Wang et al, 2013; Wang et al, 2009b), protective modulation of gut microbiota (Chang et al, 2001; Huang, 2004; Liu et al, 2014) and associated metabolic profiles (Liu et al, 2014), enhancement of T-cell differentiation, ileal cytokine production (Wang et al, 2009a) and serum IgG Ab levels (Yu, 2008).…”
Section: Lactobacilli and Bifidobacteria Prevention Of Rv Diarrhea Inmentioning
confidence: 99%